2017 11th Asian Control Conference (ASCC) 2017
DOI: 10.1109/ascc.2017.8287506
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of waste heat recovery system with fuzzy based evaporator model

Abstract: Abstract-The organic Rankine cycle (ORC) is one of the promising waste heat recovery (WHR) technologies used to improve the thermal efficiency, reduce the emissions and save the fuel costs of internal combustion engines. In the ORC-WHR system, the evaporator is considered to be the most critical component as the heat transfer of this device influences the efficiency of the system. Although the conventional Finite Volume (FV) model can successfully capture the complex heat transfer process in the evaporator, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The pressure at the expander inlet after considering the loss is shown in Figure 16. It can be seen from this figure that the expander inlet pressure for both cases of the overall model are similar except for some small deviations around time 200 s, 400 s, and 800 s. These deviations of pressure are caused by the predicting error of the evaporator outlet temperature in the fuzzy domain, which is one of the functions of the pressure loss correlation used in Equation (27). However, the error in the fuzzy-based evaporator model predicting the expander inlet pressure was only 0.001%, which is shown in Table 7.…”
Section: Results and Analysismentioning
confidence: 85%
See 1 more Smart Citation
“…The pressure at the expander inlet after considering the loss is shown in Figure 16. It can be seen from this figure that the expander inlet pressure for both cases of the overall model are similar except for some small deviations around time 200 s, 400 s, and 800 s. These deviations of pressure are caused by the predicting error of the evaporator outlet temperature in the fuzzy domain, which is one of the functions of the pressure loss correlation used in Equation (27). However, the error in the fuzzy-based evaporator model predicting the expander inlet pressure was only 0.001%, which is shown in Table 7.…”
Section: Results and Analysismentioning
confidence: 85%
“…A similar investigation carried out by Chen et al [18] indicated that up to 30% increase in the cycle efficiency is achievable if a WHR system is run at a supercritical pressure rather than a traditional subcritical pressure. The analysis and performance evaluation of supercritical ORC cycles mainly focused on fluid selections [6,15,19,20], design and optimization [15,[21][22][23][24][25][26][27]. Although steady-state models of ORC-WHR systems are necessary for the preliminary analyses as discussed above, they cannot be used either for performance evaluation in transient conditions or control system simulations.…”
Section: Introductionmentioning
confidence: 99%
“…J.I. Chowdhury et al [10] recognize the evaporator and superheater of the WHRS to be the most important component of the cement manufacturing process as it defines the efficiency of the whole process. To reduce the computational time at the evaporator in a Finite Volume model, a fuzzy based evaporator is considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This heating condition gives a good thermal match between the heat source and the working fluids, thereby improving heat recovery [4]. In recent years, the supercritical ORC has attracted a lot of attention as many publications can be found on working fluid selection [5], circuit configuration and design [6] and performance analysis and optimisation [3,[7][8][9][10][11]. However, most analyses were based on steady-state conditions only, with a limited number of publications on dynamic conditions.…”
Section: Introductionmentioning
confidence: 99%